Clinical and radiological manifestations of paraneoplastic syndrome of bronchogenic carcinoma - Goldner Branislav; Milošević Zorica; Sadiković Sead; Stojanović Milan (Srpski Arhiv za Celokupno Lekarstvo, 2005)
The objective of this study was to present some clinical and radiological manifestations of PNS in relation to bronchogenic carcinoma (BC) and to evaluate the usefulness of imaging findings in the diagnosis of asymptomatic BC. In the study group of 204 patients (146 male and 58 female) with proven bronchogenic carcinoma, PNS was present in 18 (8.62%) patients. The patients with PNS were divided into two groups. The first one consisted of 13 (72.2%) patients with symptoms related to primary tumours while the second one consisted of 5 (27.7%) patients with symptoms, at initial appearance, indicative of disorders of other organs and systems. The predominant disorder was Lambert-Eaton Syndrome, associated with small-cell carcinoma. Endocrine manifestations included: inappropriate antidiuretic hormone production syndrome (small-cell carcinoma), a gonadotropin effect with gynaecomastia and testicular atrophy (planocellular carcinoma, small-cell carcinoma), a case of Cushing Syndrome (small-cell carcinoma), and hyper-calcaemia, due to the production of the parathyroid hormone-related peptide, which was associated with planocellular carcinoma. A rare case of bilateral exophthalmos was found as PNS at adenocarcinoma. Digital clubbing and hypertrophic osteoarthropathy (HO) were associated with planocellular and adenocarcinoma, while clubbing was much more common than HO, especially among women. The differences between the two groups were related to the time of PNS appearance. In the first group, PNS occurred late on in the illness, while in the second group, PNS preceded the diagnosis of BC. Alternatively, the disappearance of a clinical or a radiological manifestation of PNS after surgery or chemotherapy may be an indicator of an improvement in health or PNS may be the first sign of illness recurrence. Radiological manifestations of PNS in asymptomatic patients may serve as a useful screen for identifying primary BC. In symptomatic patients, it may be an indicator of a higher likelihood of metastatic disease.